2011
DOI: 10.1210/jc.2011-1064
|View full text |Cite
|
Sign up to set email alerts
|

Follicle-Stimulating Hormone Receptor Polymorphism (G−29A) Is Associated with Altered Level of Receptor Expression in Granulosa Cells

Abstract: Poor ovarian response observed in subjects with the AA genotype at position -29 of the FSHR gene is due to reduced receptor expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
72
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(87 citation statements)
references
References 24 publications
14
72
0
1
Order By: Relevance
“…a Median values are given due to absence of normal distribution differ significantly between the controls and the patients (P= 0.502, P>0.05); moreover, there was no significant correlation of the SNP in the promoter region with baseline FSH, LH, E2, and PRL levels (P>0.05), which were consistent with the results of the studies of [34][35][36][37]. Acherekar et al [32] studied the −29 position in patients suffering from primary and secondary amenorrhea and found that the prevalence of AA genotypes at the −29 position was significantly higher in both amenorrheic groups as compared to the control group.…”
Section: Discussionsupporting
confidence: 82%
“…a Median values are given due to absence of normal distribution differ significantly between the controls and the patients (P= 0.502, P>0.05); moreover, there was no significant correlation of the SNP in the promoter region with baseline FSH, LH, E2, and PRL levels (P>0.05), which were consistent with the results of the studies of [34][35][36][37]. Acherekar et al [32] studied the −29 position in patients suffering from primary and secondary amenorrhea and found that the prevalence of AA genotypes at the −29 position was significantly higher in both amenorrheic groups as compared to the control group.…”
Section: Discussionsupporting
confidence: 82%
“…This observation contradicts various studies conducted on c.2039 A>G [5][6][7][8][9][10][11] but is similar to others [12][13][14][15][16][17]. In the studies focusing on c.-29 G>A polymorphism, no correlation was found with basal FSH [4,[28][29][30]; this was in line with our observation.…”
Section: Discussionsupporting
confidence: 60%
“…On the other hand, and with reference to the paper by Achrekar et al [29], patients with the A/A variant required a higher total dose of gonadotropins in order to reach significantly lower levels of estradiol on the day of hCG administration with a lower number of retrieved oocytes. The preliminary results of this study were subsequently confirmed with a demonstrated reduction in FSHR gene expression in granulosa cells [30]. By considering the association of the c.2039 A>G and c.-29 G>A polymorphisms, it has been proven that 75% of the patients with the combination A/A-A/A were poor responders, with a significant decrease in this category of FSHR expression in granulosa cells [31].…”
Section: Introductionsupporting
confidence: 67%
See 2 more Smart Citations